Effects of Low-Volume High-Intensity Interval Training Compared to Moderate-Intensity Continuous Training on Inflammatory Profile in Women with Type 2 Diabetes. Issue 3 (2022) - Marcotte-Chénard, Alexis; Tremblay, Renaud; Mony, Marie-Michelle; Tremblay, Dominic; Boulay, Pierre; Brochu, Martin
No abstract available